2017
DOI: 10.1177/2050313x17720627
|View full text |Cite
|
Sign up to set email alerts
|

Acute aortic occlusion due to tumor embolism in a patient with lung malignancy

Abstract: Objectives:Acute lower limb ischemia caused by tumor embolization is rare, despite the fact that cancer is a common cause of hypercoagulability predisposing to venous thrombosis. Arterial embolization is mostly associated with intracardiac tumors while lung malignancies are the second most common cause of tumor embolism.Methods:In this report, we present a male patient who developed acute bilateral lower limb ischemia in the immediate postoperative period after a thoracotomy for attempted left upper lobe resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…The embolization of tumor fragments significant enough to cause ischemia, however, is a rare event. 1 , 2 , 3 , 4 , 5 , 6 , 7 The first case was described in 1981 by Starr et al. 1 Compared with ischemic events that occur from unknown malignant sources, those from known malignant sources have been more widely recognized for two main reasons.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The embolization of tumor fragments significant enough to cause ischemia, however, is a rare event. 1 , 2 , 3 , 4 , 5 , 6 , 7 The first case was described in 1981 by Starr et al. 1 Compared with ischemic events that occur from unknown malignant sources, those from known malignant sources have been more widely recognized for two main reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all reports of systemic arterial embolization in patients with any primary malignancy have discussed the mechanism by which pulmonary metastases, pulmonary primary tumors, or cardiac malignancies invade the pulmonary veins (PVs), fragment within the left atrium or within the PVs and subsequently enter the systemic circulation. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 Another recognized mechanism is when the heart or aorta has been directly invaded by the tumor owing to proximity, achieving direct access to the arterial circulatory system. 4 , 5 , 6 , 7 , 8 , 9 Finally, in patients with known invasive lung cancer undergoing surgery, it has been reported that surgical manipulation of the PVs can result in arterial embolization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations